Dear Leader!: A Look at (In)directness in Online Complaints in China - Shiying Zhao; Ridwan Wahid (UIN Salatiga, 2024)
The rise of e-government services has led to an increase in citizens interacting with the government online. However, not much about the nature of citizen complaints on such administrative platforms is known. The few previous studies have shown that due to politeness considerations, Chinese communication is often indirect in power-asymmetrical settings. This study examines citizen complaint posts on an online e-service platform in China, exploring the linguistic directness and politeness of those posts. Using a qualitative method, 300 citizen complaint posts were analyzed, with the findings revealing that: a) traditional markers of politeness were not extensively used in the opening and closing of complaint posts despite their inherently face-threatening nature; b) citizens communicated directly with the government, expressing a high level of directness in complaint posts; c) despite finding (b), complaint components were not in general perceived as impolite. The paper argues that Chinese communication is not always indirect, particularly in online situations where there is a power imbalance. In such cases, citizens sporadically use traditional politeness markers such as politeness strategies, specific types of speech act components, and avoidance of expressions of negative emotions. Interestingly, the study found that citizens focused more on avoiding Component B (i.e. dissatisfaction/disapproval) in complaints and formalizing complaint components, rather than relying on traditional politeness strategies to express politeness. In this online administrative context, direct citizen-to-government (C2G) communication is transaction-oriented and instrumental in nature. This paper provides some insight into Chinese pragmatics and practical guidelines for citizens to make successful and efficient complaints in an online administrative context.